Scottish Literature of the South Seas : Critical Studies of Scotland and the Pacific - Francis, Allison E.,; Hill, Richard J., (Literature and Cultural Studies E-Books Online, Collection 2025., 2025)
This volume, edited by Richard J. Hill and Allison E. Francis, explores literary connections between Scotland and the Pacific. The contributors, including some of the world's foremost scholars in Scottish and Pacific studies, examine how Scottish writing about the Pacific, and Pacific engagement with Scottish culture, generates a cultural examination of Scotland's place in the British colonizing hierarchy. While Robert Louis Stevenson was the principal Scottish author who shaped these early discussions, other prominent Scottish authors are also analyzed. Several chapters examine Scottish engagement with the South Seas, before and after Stevenson's involvement with Pacific cultural and political affairs. The book lends weight and understanding as to why Pacific Islanders-both immigrant and indigenous-often claim affiliations with Scotland, and in the case of Hawaii and Samoa, to Stevenson in particular. See Less